ANALISIS PENGGUNAAN MODAL KERJA DALAM MENINGKATKAN PROFITABILITAS DI KOPERASI RUKUN KARYA LUBUKLINGGAU - Herman Paleni; Astri Riance; Indriany Widiastuty (LPPM UNIVERSITAS BINA INSAN, 2018)
Provision of credit facilities have a level of risk that the possibility of credit can not be billed, then it is necessary the correct credit analysis by employee cooperatives. Referred to as problem loans because the debtor has a delay in returning the credit. Bad credit should be quickly resolved to avoid greater losses. The purpose of this study is to find out how the analysis of bad loans using the method 5c on the cooperative savings and loan